METHOTREXATE IN THE TREATMENT OF COXITIS IN EARLY SPONDYLOARTHRITIS: ARE THERE PROSPECTS? - T. V. Dubinina; A. B. Demina; Sh. F. Erdes (Научно-практическая ревматология)
Hip joint injury, coxitis, is a characteristic manifestation of ankylosing spondylitis. Coxitis therapy has not been elaborated so far. There are few publications on the efficacy of tumor necrosis factor-α inhibitors. Alternative pharmacotherapies, including use of methotrexate, have not fully been studied. The study describes clinical cases of coxitis treated in patients with early spondyloarthritis.